Chronic Burkholderia cepaciabronchiectasis in a non-cystic fibrosis individual. Issue 5 (1st May 1998) - Ledson, M J; Gallagher, M J; Walshaw, M J
Abstract : Infection with Burkholderia cepacia due to social contact is well described in patients with cystic fibrosis. However, social transmission to non-cystic fibrosis individuals or chronic colonisation in non-cystic fibrosis individuals has not been described. A report of B cepacia bronchiectasis is presented where a previously healthy mother of two cystic fibrosis children colonised with B cepacia became infected by the same epidemic strain. The implications of this for parents, siblings, and partners of individuals with cystic fibrosis are discussed.